The effect of land use intensity and habitat characteristics on butterfly community composition within the Southern Great Plains of the United States - Emily A. Geest; Raymond A. Moranz; Kristen A. Baum (Grassland Research)
Abstract Background As grasslands decline, grassland‐dependent species such as grassland butterflies have experienced widespread population losses. To manage remaining grasslands, prescribed fire, grazing, and haying are common management practices across the Southern Great Plains of the United States. However, the impacts of management and land use intensity (LUI) on butterfly community composition and butterfly community traits are not well understood. Additionally, local habitat characteristics such as vegetation height and cover, as well as broader landscape categorization, including how much agriculture or urbanization is occurring around the habitat, can alter butterfly communities. Methods We conducted standardized butterfly and flowering forb surveys at grassland sites across north‐central Oklahoma. Results LUI influenced overall butterfly community composition with sites managed only with fire having the most dissimilar butterfly community compared to three other management regimens. The amount of agriculture, urbanization, and wetlands surrounding study sites also influenced butterfly community composition. Flowering forb community measures differed by site with sites managed by fire alone having lower blooming forbs species richness, diversity, and abundance than sites with other management regimens. Conclusions Sites managed with only prescribed fire had the most disparate butterfly community in comparison to other management methods, suggesting that specialist butterfly species may be sensitive to increasing disturbance.